Impact of Physical and Mental Training on Overall Performance and Sports Injury Prevention in Female Volleyball Athletes (Indian Journal of Physiotherapy and Occupational Therapy - An International Journal, 2021)
The goal of this study was to assess and investigate the Impact of the Physical & Mental training on thephysical fitness, competitive anxiety level and self-confidence of Female Volleyball Athletes in order toprevent the chances of injury during Volleyball and to educate the proper techniques for the sports injuryprevention. A total of 35 participants were included in the study after clearing functional movement screening(FMS). The participants were assessed pre and post the study to find the result and prove the hypothesis.The scales used were SCAT, TSCI, AAHPER. The participants were undergone 11 weeks interval trainingsession. The pre and post results were analyzed on T-Test and Percentage analysis. The findings of presentstudy show that in 35 participants 66% of the participants had shown improvement in the confidence levelafter the training whereas 71 % had shown improvement in the anxiety level after the training. On analyzing6 components of motor fitness on the basis of AAHPER Motor fitness test, 77% got benefitted in the SitUps training, 91 % got benefitted in flexed arm hang training. 66% had shown improvement in shuttlerun training. 54 % participants had shown improvement in standing long jump and 600-yard run trainingwhereas 51 % participants had shown improving in 50-yard dash training.Conclusion: On analyzing the physical fitness through AAHPER scale, the pre post results were highlysignificant which proves the physical training sessions of 11 weeks were effective in the improvement ofthe physical fitness of female Volleyball players. The Confidence level were remarkably improved aftertraining sessions as the T test pre post analysis was highly significant. The anxiety level of the participantswas shown improvement in the percentage analysis when they were assessed pre and post training sessionsthrough SCAT Scale. On the basis of the findings, it can be concluded that Interval Training session (Physicaland Mental) are effective on the overall performance of Female Volleyball Athletes.
Keywords: Volleyball Athletes, Confidence, Anxiety, Physical Fitness, Physical training, mental training.